PENGARUH PENDAPATAN ASLI DAERAH, DANA PERIMBANGAN, DANA KEISTIMEWAAN DAN BELANJA MODAL TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH: Studi Kasus pada Pemerintahan Daerah Kabupaten dan Kota di Daerah Istimewa Yogyakarta Tahun Anggaran 2013-2018 - Nanda Dipa Prastiwi; Andri Waskita Aji (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2020)
The purpose of this study was to determine: (1) the effect of regional own-source revenue (PAD) on the financial performance of district / city governments in the Special Region of Yogyakarta (DIY), (2) the effect of balancing funds on the financial performance of district / city governments in the Special Region provinces Yogyakarta (DIY) and (3) the effect of privileged funds on the financial performance of district / city governments in the Special Region of Yogyakarta (DIY), (4) the effect of capital expenditure on the financial performance of district / city governments in the province of Special Region of Yogyakarta (DIY). This report uses the Realization of the 2013-2018 Regional Revenue and Expenditure Budget (APBD), which is published through the website of the regency / city Central Statistics Agency (BPS). Government financial performance is measured by the ratio of regional financial independence. The sample used is 30 data. To test the effect of regional own-source revenue, balance funds, privileged funds and capital expenditure on government financial performance using multiple linear regression analysis. The results of the study show that: (1) regional own-source revenue (PAD) has a positive effect on financial performance, (2) balancing funds has a negative effect and (3) the special fund does not have a negative effect on the financial performance of the district / city government in the Yogyakarta Special Region (DIY), (4) capital expenditure does not have a positive effect on the financial performance of the district / city government in the province of the Special Region of Yogyakarta (DIY).